Microwave Assisted Rapid Extraction and Characterization of Coumarin from Fig Plant (Ficus carica) - Mohan, Resmi; Vidhyalakshmi, M.; Sivakumar, Venkatasubramanian (Asian Journal of Science and Applied Technology, 2019)
Coumarins are fragrant natural bioactive organic compound find application as aroma, flavor and wide medicinal use. Fig plant (Ficus Carica) is a very good source of Coumarins. Coumarins are a member of the benzopyrone family and it has a benzene ring joined to a pyrone ring. There is a need for effective extraction and purification of Coumarins from plant materials. Different methods of extraction of Courmarin from Ficus Carica has been studied in this paper, among them, microwave extraction (180 W power) provided rapid extraction with 10 minutes time with extract yield of 0.67 g as compared to that of 1 hour of water bath extraction at 60C. Coumarin was isolated from the crude extract using NaOH and petroleum ether and their presence was characterized confirmed using UV spectroscopy, IR spectroscopy, TLC and fluorescence test. The antibacterial activity of coumarin was also evaluated using disc diffusion method and Minimum Inhibition Count (MIC). The present study analyzes and provides method of microwave assisted rapid extraction of Coumarin from Fig plant (Ficus Carica) and its characterization, which could be widely used as generic method from natural materials for different applications.